The Contribution of Interpersonal Communication to Student Adjustment - Shintya Tias Triyulianis; Indra Ibrahim (Universitas Negeri Padang, 2019)
This research is motivated by the phenomenon of many students who tend to be difficult to adjust. The effectiveness of self-adjustment will determine the objectives to be achieved in fact there are still many students who are not able to adjust themselves well in the school environment, this is dilator behind by interpersonal communication which is one of the factors that is suspected to influence student adjustment. This study aims to describe: 1) Interpersonal Communication, 2) self-adjustment, and 3)The contribution of Interpersonal Communication to student self-adjustment.This type of research is a descriptive correlational research, with a quantitative approach. The sample in this study were 200 students consisting of classes X and XI, selected by Stratifate random sampling technique. The instrument used was Scale using Linkert scale mode. Data were analyzed with descriptive statistics and simple linear regression.The findings of this study show that: 1) most interpersonal communication students of SMK N 10 Padang have high levels of interpersonal communication, even though there are students who have very high, medium and low levels of interpersonal communication. There are no students who have a low level of adjustment and are very low. 2) Most adjustment of students of SMK N 10 Padang has a fairly good level of adjustment, even though there are students who have a very good and good level of adjustment. There are no students who have a level of adjustment that is lacking and lacking once. 3) There is a significant contribution between interpersonal communication with the adjustment of students of SMK Negeri 10 Padang, which is 13.9%.